Глобальна гендерна нерівність: головні тенденції - Степанченко, К. І. (ХНУРЕ, 2022)
This publication presents the results of a study aimed at identifying trends in overcoming global gender inequality. To achieve this goal, the author clarified the concept of "gender gap", analyzed the gender gap index and data on the gender gap in the economy, politics, education and health in the world and Ukraine, which are contained in the reports of the World Economic Forum for 2018-2021.
Keywords: гендерна нерівність